The place of Education in the Formation of the Landless Subject's Identity - Mayara Duarte Pelegrini; Maria Simone Ferraz Pereira (Universidade Federal do Norte do Tocantins, 2022)
This paper discuss the Landless Workers Movement (MST), and the constitution of the identity of these subjects belonging to the movement, seeking to envision the social movement as a formative principle. Through a bibliographic survey, it was discussed how social movements are constituted in a conjuncture of dispute, being essentially, political-social processes. We emphasize that the MST is born from concrete struggles, from subjects who, by living in their skin, rebelled against the processes of exclusion, engendered by the neoliberal capitalist model. Through the struggle for land and its dynamics of organization and initiatives, based on collectivity and belonging to the social movement, the MST presents the possibility of building a new popular development project for the country. The formation of landless subjects takes place in the experiences within the movement, which gives them a greater meaning than the individual, and inserts them into a common perspective of life, and thus, talking about an educational project from/to the countryside, it means thinking about the subjects who fight and work on the land, and see their life and work in it. The formation in this context is a human doing, which builds and is built in a movement, of social struggle.